Sensitiviy analysis.xlsx - Gutierrez-Carazo, Encina (Cranfield University, 2022)
Sensitivity analysis of the influence of density, tortuosity, porosity, partition coefficient and flowrate on the transport of NTO in sand.
Keywords: 'Sensitivity analysis'; 'GoldSim'; 'soil physico-chemcial propoerties'